Degree of job satisfaction when teaching geography from their point of view (Journal of the College of Basic Education, 2020)
The current research aims to know the degree of job satisfaction when teaching the geographical department from their point of view, and in order to achieve this goal the researcher used the descriptive curriculum, be the research community of the department of geography faculty of basic education University mustine for the academic year (2020-2019), prepared the researcher Resolution as a tool for its research has been verified its sincerity and stability and has become composed of (24) paragraphs. The researcher used a range of statistical methods, including mathematical circles, standard deviations and T-testing for independent samples. The research reached a set of results, including paragraph (2) ranked first and high, while paragraph (16) came in the last 24th and low. After using the T-test for two independent samples to identify the presence of statistically significant differences at the level of significance of 0.05) between the vertebrae of the sex variable, the results of the current research indicated that there are statistically significant differences at the level of significance of 0.05) in favor of females. The research reached a number of recommendations, including: - the need to guide those concerned in the Ministry of Higher Education and Research